MAJAS DALAM HAIKU KARYA MATSUO BASHO - Badai Tris Suhendar; Umul Khasanah (Mezurashii: Journal of Japanese Studies, 2020)
Abstrak: Tulisan ini memaparkan hasil analisis majas yang terkandung dalam Haiku (puisi Jepang) karya Matsuo Basho dalam buku Basho’s Haiku: Selected Poems of Matsuo Basho. Haiku-haiku tersebut sebagian merupakan catatan perjalanan semasa hidupnya. Di dalam 40 haiku yang dianalisis, didapati bahwa majas perbandingan adalah yang paling banyak digunakan.  Di dalamnya, metafora adalah majas yang paling banyak digunakan, yakni 15 kali. Selain itu ada pula majas personifikasi (6), hiperbola (5), alegori (4), dan simile (3). Selain itu ditemukan pula bahwa dalam beberapa haiku, Basho menggunakan lebih dari satu majas.Kata kunci: Stilistika, Majas, Haiku, Matsuo Basho Abstract: This paper discussed about figure of speech in Haiku (Japanese poems) written by Matsuo Basho in Basho’s Haiku: Selected Poems of Matsuo Basho. Some of his haiku are the record of journey during his life. In 40 haiku analyzed, metaphor is the most used figure of speech, that is 15 times. Aside from that, personification 6 times, hyperbole 5 times, allegory 4 times, and simile 3 times. It is also found that in some of haiku, Basho used more then one figure of speech. Keywords: stylistics, figure of speech, haiku, Matsuo Basho